Knowledge and perception of pelung keepers’s toward chicken contests in West Java, Indonesia - INDRAWATI Y. ASMARA; DANI GARNIDA; MARINA SULISYTATI; SAFITRI TEJANINGSIH; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2018)
Asmara IY, Garnida D, Sulisytati M, Tejaningsih S, Partasasmita R. 2018. Knowledge and perception of pelung keepers’s toward chicken contests in West Java, Indonesia. Biodiversitas 19: 2232-2237. Pelung chicken is an indigenous chicken breed which has social and cultural functions in particular communities in Indonesia. Contests are conducted regularly as a media to show the singing ability of Pelung chickens and the activities are considered important to maintain the existence of the chickens. The objective of this study was to determine the knowledge and perceptions of chicken keepers toward chicken contests for Pelung chickens. A survey using open and structured questionnaire was conducted to collect data involving 133 Pelung keepers. The study was carried out in four districts in West Java Province, Indonesia including Cianjur, Sukabumi, Bandung, and Garut Districts. The data were analyzed using descriptive analysis. The result showed that almost respondents knew about contests and they defined contests as a media to find good breeds as well as a media to find and/or improve networks. Main sources of information contests were the organization, family, and social media. Respondents had positive perception toward contests, and they actively participated in the different level of contests. The findings are important as social input for the management of animal genetic resources (AnGR) in Indonesia